Response to Improvement of Arterial Stiffness in the Transition From Acute Decompensated Heart Failure to Chronic Compensated Heart Failure. Issue 9 (2nd July 2013) - Yalcinkaya, Emre; Celik, Murat; Yasar, Salim; Bugan, Baris
<x xml:space="preserve">Abstract</x> Kim DB et al. Clin Cardiol. 2013;36:358–362.